(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The aim of this study is to examine the Role of Taxation in Sustainable Development. Taxation is a pivotal instrument in advancing sustainable development, influencing economic, social, and environmental outcomes. Sustainable development aims to harmonize economic growth with social equity and environmental stewardship to ensure long-term well-being for current and future generations. Taxation plays a crucial role in achieving this balance by directing resources, incentivizing desirable behaviors, and funding essential services and infrastructure. Environmental taxes, such as carbon taxes and pollution levies, internalize the costs associated with environmental degradation, encouraging businesses and individuals to adopt more sustainable practices. These taxes help mitigate the adverse effects of pollution and resource depletion, supporting the transition to a greener economy. Additionally, tax incentives for renewable energy investments and energy-efficient technologies stimulate innovation and the adoption of sustainable solutions. Progressive tax systems contribute to social equity by redistributing wealth and funding social programs, such as healthcare and education, which enhance public welfare and reduce income inequality. This redistribution supports a more stable and inclusive society, aligning with sustainable development goals. Taxation also drives behavioral change by altering economic incentives. Taxes on harmful goods, such as sugary drinks or single-use plastics, can reduce consumption and promote healthier and more environmentally friendly alternatives. This behavioral shift not only addresses public health and environmental issues but also supports the broader objectives of sustainable development. Taxation serves as a strategic tool for fostering sustainable development by aligning economic incentives with environmental and social goals. Through effective tax policies, governments can generate revenue, promote equitable growth, and support environmental protection, ultimately contributing to a more sustainable and resilient future.